Effect of Gap and Shims on the Strain and Stress State of the Composite-Aluminum Hybrid Bolted Structure. (9th December 2020) - Yue, Xuande; An, Luling; Ye, Xin; Wang, Chufan; Cai, Yuebo; Xiao, Ruiheng
Abstract : The composite-aluminum hybrid bolted structures are widely used in aircraft. Due to low molding accuracy of composite components, gaps always occur between components during assembly. In this case, the bolt connection can cause a complex strain and stress state of component. It may adversely affect the mechanical properties or cause local damage of the structure. A simplified model of the composite-aluminum assembly structure was established in this paper. Then, the influence of forced assembly, liquid shim, and peelable fiberglass shim on the strain and stress state of the composite-aluminum hybrid bolted structure was studied. A bolt connection experimental device was designed to apply a preload to the specimen. The strain field on the specimen surface was measured using the 3D-DIC strain measurement system. The finite element model was established to study the interlaminar stress and damage state of composite laminates. It is found that the strain of specimen in the X -direction is mainly affected by the bending deformation, while the strain in the Y -direction is mainly affected by the compression of bolt head. For composite laminates, the strain value in the X -direction can be reduced by 8.31%-70.97% with shims. As for the strain value in the Y -direction, the liquid shim can only reduce it up to 23.93%when the gap is large. In addition, the liquid shim and peelable fiberglass shim cannot reduce the stress value of all interlaminar elements, but it can make the stress distribution more uniform and improve the stress state of the interlaminar element when the shim was more than 0.8 mm.